Enhanced cross-recognition of SARS-CoV-2 Omicron variant by peptide vaccine-induced antibodies - Aparicio, Belén; Ruiz, Marta; Casares, Noelia; Silva, Leyre; Egea, Josune; Pérez, Patricia; Albericio, Guillermo; Esteban, Mariano; García-Arriaza, Juan; Lasarte, Juan J.; Sarobe, Pablo (Frontiers in Immunology, 2023)
Current vaccines against SARS-CoV-2, based on the original Wuhan sequence, induce antibodies with different degrees of cross-recognition of new viral variants of concern. Despite potent responses generated in vaccinated and infected individuals, the Omicron (B.1.1.529) variant causes breakthrough infections, facilitating viral transmission. We previously reported a vaccine based on a cyclic peptide containing the 446-488 S1 sequence (446-488cc) of the SARS-CoV-2 spike (S) protein from Wuhan isolate. To provide the best immunity against Omicron, here we compared Omicron-specific immunity induced by a Wuhan-based 446-488cc peptide, by a Wuhan-based recombinant receptor-binding domain (RBD) vaccine and by a new 446-488cc peptide vaccine based on the Omicron sequence. Antibodies induced by Wuhan peptide 446-488cc in three murine strains not only recognized the Wuhan and Omicron 446-488 peptides similarly, but also Wuhan and Omicron RBD protein variants. By contrast, antibodies induced by the Wuhan recombinant RBD vaccine showed a much poorer cross-reactivity for the Omicron RBD despite similar recognition of Wuhan and Omicron peptide variants. Finally, although the Omicron-based 446-488cc peptide vaccine was poorly immunogenic in mice due to the loss of T cell epitopes, co-immunization with Omicron peptide 446-488cc and exogenous T cell epitopes induced strong cross-reactive antibodies that neutralized Omicron SARS-CoV-2 virus. Since mutations occurring within this sequence do not alter T cell epitopes in humans, these results indicate the robust immunogenicity of 446-488cc-based peptide vaccines that induce antibodies with a high cross-recognition capacity against Omicron, and suggest that this sequence could be included in future vaccines targeting the Omicron variant.